Physiological quality of seeds of white oat cultivars in response to trinexapac-ethyl application - Bazzo, José Henrique; Barbosa, André; Cardoso, Carolina; Zucareli, Claudemir; Fonseca, Inês Cristina (Revista Ciência Agronômica, 2018)
The aim of this study was to assess the effect of the growth retardant trinexapac-ethyl on the physiological quality of seeds of different grain white oat cultivars in two growing environments. The experiments were carried out in Londrina and Mauá da Serra, Paraná State, Brazil. The experimental design was a randomized block design in a 4 × 2 factorial scheme with four replications. Treatments consisted of four white oat cultivars (IPR Afrodite, IPR Artemis, URS Corona, and URS Guria), with and without growth retardant application. Trinexapac-ethyl was applied by foliar spraying in a dose of 125 g a.i. ha−1 at the stem elongation stage between the first and second perceptible node. The following parameters were assessed: germination, first germination count, length and dry matter of seedling shoot and root, accelerated aging, electrical conductivity, emergence rate index, seedling emergence in sand, one-thousand-seed weight. At the end of the study, Londrina and Mauá da Serra presented a production potential white oat seed with germination above the standards for the species. Trinexapac-ethyl application reduced seed vigor of the cultivars IPR Afrodite and IPR Artemis produced in Londrina and Mauá da Serra, respectively.